2008
DOI: 10.1371/journal.pone.0003299
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Protein-Protein Interactions and Involvement of Viral Proteins in SARS-CoV Replication

Abstract: Analyses of viral protein-protein interactions are an important step to understand viral protein functions and their underlying molecular mechanisms. In this study, we adopted a mammalian two-hybrid system to screen the genome-wide intraviral protein-protein interactions of SARS coronavirus (SARS-CoV) and therefrom revealed a number of novel interactions which could be partly confirmed by in vitro biochemical assays. Three pairs of the interactions identified were detected in both directions: non-structural pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
204
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(224 citation statements)
references
References 73 publications
16
204
4
Order By: Relevance
“…Apparently, in the context of a viral infection, when other viral proteins are present, MHV nsp2 and HCV NS5A are immobilized at the replicative structures presumably due to protein-RNA or protein-protein interactions. In agreement herewith, large-scale protein-protein interaction studies demonstrated that nsp2 of MHV and SARS-CoV is engaged in a multitude of interactions with itself, nsp3, nsp4, nsp6, nsp7, nsp8, nsp11, nsp15 and nsp16 [82,114,115,116]. These observations are remarkable in view of the dispensability of nsp2 during CoV infection in vitro [59].…”
Section: Dynamics Of Cov Replicative Structures and Associated Prosupporting
confidence: 76%
See 1 more Smart Citation
“…Apparently, in the context of a viral infection, when other viral proteins are present, MHV nsp2 and HCV NS5A are immobilized at the replicative structures presumably due to protein-RNA or protein-protein interactions. In agreement herewith, large-scale protein-protein interaction studies demonstrated that nsp2 of MHV and SARS-CoV is engaged in a multitude of interactions with itself, nsp3, nsp4, nsp6, nsp7, nsp8, nsp11, nsp15 and nsp16 [82,114,115,116]. These observations are remarkable in view of the dispensability of nsp2 during CoV infection in vitro [59].…”
Section: Dynamics Of Cov Replicative Structures and Associated Prosupporting
confidence: 76%
“…CoV replicative structures/RTCs are macromolecular assemblies, the components of which are engaged in a plethora of protein-protein, protein-RNA, and protein-lipid interactions [114,115,116,131]. Currently, the exact composition of the replicative structures/RTCs is not known, let alone the full arsenal of interactions occurring within these structures.…”
Section: Future Directionsmentioning
confidence: 99%
“…Impact of nsp10 IDAs on the Interaction with nsp16 in Mammalian Cells-Interaction of nsp10 with nsp16 has already been detected in mammalian cells using the two-hybrid system and confirmed using pull-down assays (26). However, mammalian two-hybrid systems detect interaction within the cell nucleus, whereas these viral proteins are localized in the cytoplasm during infection.…”
Section: Delineation Of the Nsp10 Surface Involved In Its Interactionmentioning
confidence: 92%
“…with nsp16-We used RY2H with nsp10 and nsp16 to isolate interaction-defective alleles (IDAs) and thereby delineate their surface of interaction (25,26). IDAs are alleles that contain mutations affecting their ability to interact with their wild type binding partners, leading to the identification of specific amino acid residues involved in the interaction between nsp10 and nsp16 (39).…”
Section: Delineation Of the Nsp10 Surface Involved In Its Interactionmentioning
confidence: 99%
“…pCMV-tag2b-N was constructed as described [15]. pCMV-Myc-N was constructed by substituting the Flag-tag coding sequence of pCMV-tag2b-N with Myc-tag coding sequence.…”
Section: Plasmidsmentioning
confidence: 99%